Coronary Artery Bypass Surgery in Left Main Disease with Idiopathic Artery Pulmonary Hypertension. Role of PGE Therapy - Walter Serra; Igino Spaggiari; Alessandro Maria Budillon; Filippo Benassi; Giorgio Romano; Tiziano Gherli; Antonella Vezzani; Tullio Manca (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2016)
Idiopathic pulmonary hypertension (PAH) is a rare disease of unknown etiology that leads to the development of severe precapillary pulmonary hypertension [1-3], characterized by impaired regulation of  both  pulmonary hemodynamics  and  vascular  growth. The responsiveness to vasodilator therapy in patients with PAH varies considerably [4,5]. Coronary artery bypass grafting (CABG) with extracorporeal circulation has a deleterious effect on lung tissues. Left coronary artery could be compressed by the enlargement of the main pulmonary artery. Postoperative pulmonary hypertension contributes to increased perioperative mortality and in patients  undergoing CABG, was the only independent variable able to predict postoperative mortality. To date,  right ventricular dysfunction, as surgical risk score, is not considered. The main pathophysiologic mechanism of this dysfunction is the afterload mismatch. The right ventricular (RV) contractility is increased, but not enough compared to the afterload.